J Journalists’ Workplace Safety Protection during Demonstrations (INTEGRATION PROCEEDING, 2023)
In terms of connecting his life every human being needs a job. Human life is considered more prosperous when getting a decent job. Workers in carrying out their work in addition to getting wages, of course, need to get legal protection and work safety protection. There are many workers who work in dangerous areas, one of them is a journalist. Journalists in reporting for the sake of news that will be broadcast to the public or the audience, sometimes the coverage area is included in dangerous areas such as demonstrations or rallies. Demonstrations or rallies often end in chaos, in this case it is certain that many journalists from various media come to cover the demonstration. It is not uncommon for journalists to also get bad effects from such demonstrations such as accidents during demonstrations against journalists. In demonstrations the safety of journalists needs to be accounted for, because it is the journalists bet their lives for the sake of covering the news about the demonstration. Workers have the right to safety in their work area from the above problems in this study, the formulation of the problem can be raised, namely how is the form of occupational safety protection for journalists at the time of the demonstration?. This study uses normative legal methods in which there is a lack of clarity on the regulation of occupational safety protection for journalists, especially when covering demonstrations. The purpose of this study is to know the form of occupational safety protection for journalists and of course provide full protection of Occupational Safety for journalists, especially when covering demonstrations. The solution that can be given is to clarify the regulations about who is responsible if journalists have an accident, especially when covering demonstrations.